ENHANCING ENGLISH LANGUAGE COMPETENCE IN SCHOLARLY WRITING SKILLS: THE IMPACT OF RESEARCH WRITING RETREATS ON EMERGING RESEARCHERS IN HIGHER EDUCATION - Bulelwa Makena; Thandiswa Mpiti (PEDAGOGIK : JURNAL PENDIDIKAN, 2024)
This study outlines the challenges faced by students that lead to system stagnation when they encounter difficulties in completing their research reports within the expected timeframe. Inadequate English language competence is a major factor likely to hinder the progress and success of most authors referred to as 'emerging researchers.' Therefore, this research aims to understand the pedagogical impact of research writing on enhancing scholarly writing skills and improving English language proficiency for emerging authors. This study employs a qualitative research approach with a case study design. This approach aims to understand real-life circumstances involving the subjects under investigation. Semi-structured interviews were used to collect data. The data were analyzed using Miles and Huberman's data analysis techniques, which include data reduction, data display, and verification. The research results show that the pedagogical impact of research writing in improving scientific writing skills and improving English language skills is increasing pedagogical skills in English academic writing and increasing the level of publication of research results.